Analisis Kesiapan UMKM Syariah dalam Memanfaatkan Platform E-Commerce untuk Pemasaran Produk Halal - Anisa Putri; Ely Yuliana; Azza Nuha Nisrina; Achmad Zakari; Aldi Khusmufa Nur Iman (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
Sharia-based Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting national economic growth and developing a competitive halal value chain, yet they still face challenges such as limited digital literacy, restricted access to halal certification, and insufficient marketing strategies aligned with sharia principles. This study aims to analyze the readiness of Sharia MSMEs in utilizing e-commerce platforms as a medium for halal product marketing through a systematic literature review of 50 articles from accredited national journals and reputable international publications. The findings reveal that Sharia MSME readiness is influenced by internal factors, including digital literacy, halal certification, branding strategies, and sharia compliance, as well as external factors such as government policies, digital ecosystem support, and consumer trust. The study highlights the importance of accelerating halal certification, strengthening human resource capacity, and implementing value-based marketing strategies to enhance competitiveness. The implications suggest that synergy among MSMEs, government, and digital platform providers is essential to create an inclusive and sustainable halal ecosystem, enabling Sharia MSMEs to compete effectively in both local and global markets.